Exosomes derived from miR‐375‐overexpressing human adipose mesenchymal stem cells promote bone regeneration. (5th August 2019) - Chen, Si; Tang, Yiman; Liu, Yunsong; Zhang, Ping; Lv, Longwei; Zhang, Xiao; Jia, Lingfei; Zhou, Yongsheng
Abstract: Objectives: The present study aimed to investigate whether exosomes derived from miR‐375‐overexpressing human adipose mesenchymal stem cells (hASCs) could enhance bone regeneration. Materials and Methods: Exosomes enriched with miR‐375 (Exo [miR‐375]) were generated from hASCs stably overexpressing miR‐375 after lentiviral transfection and identified with transmission electron microscopy, nanosight and western blotting. The construction efficiency of Exo (miR‐375) was evaluated with qRT‐PCR and incubated with human bone marrow mesenchymal stem cells (hBMSCs) to optimize the effective dosage. Then, the osteogenic capability of Exo (miR‐375) was investigated with ALP and ARS assays. Furthermore, dual‐luciferase reporter assay and western blotting were conducted to reveal the underlying mechanism of miR‐375 in osteogenic regulation. Finally, Exo (miR‐375) were embedded with hydrogel and applied to a rat model of calvarial defect, and μ‐CT analysis and histological examination were conducted to evaluate the therapeutic effects of Exo (miR‐375) in bone regeneration. Results: miR‐375 could be enriched in exosomes by overexpressing in the parent cells. Administration of Exo (miR‐375) at 50 μg/mL improved the osteogenic differentiation of hBMSCs. With miR‐375 absorbed by hBMSCs, insulin‐like growth factor binding protein 3 ( IGFBP3 ) was inhibited by binding to its 3′UTR, and recombinant IGFBP3 protein reduced the osteogenic effects triggered by Exo (miR‐375). After incorporated with hydrogel, Exo (miR‐375) displayed a slow and controlled release, and further in vivo analysis demonstrated that Exo (miR‐375) enhanced the bone regenerative capacity in a rat model of calvarial defect. Conclusions: Taken together, our study demonstrated that exosomes derived from miR‐375‐overexpressing hASCs promoted bone regeneration.